National Climate-Smart Agriculture and Food Security Action Plan of Ghana (2016-2020) - Owuso Essegbey, George; Nutsukpo, D.K.; Karbo N; Zougmoré, Robert B. (2015)
The policy document – National Climate-Smart Agriculture and Food Security Action Plan of Ghana (2016-2020) – provides the implementation framework for an effective development of climate-smart agriculture in the ground. It formulates specific strategies that will contribute developing climate-resilient agriculture and food systems for all agro-ecological zones, as well as the human resource capacity required for a climate-resilient agriculture promotion in Ghana. The action plan is therefore an effort to translate to the ground level the broad national goals and objectives in climate-smart agriculture. Its development has been made possible through the active engagement of various public and private institutions and organizations in Ghana. The methodology comprised desk research, data collection through interviews and participatory workshops and small group meetings. A review of relevant agricultural policy documents such as the Food and Agriculture Sector Development Policy (FASDEP), the METASIP and the Agriculture Sustainable Land Management Strategy and Action Plan was done to analyse the current national agricultural policy environment. Participatory workshops were organized to bring representatives of stakeholder organizations together to discuss various components of the action plans and prepare inputs. These stakeholder consultation workshops were used to carry out prioritization of the action areas by the agro-ecological groupings. The stakeholders included farmers, small-scale agro-entrepreneurs, women groups and local government authorities. In addition, a validation workshop was held to provide a platform for a final discussion of the draft Action Plan with key stakeholders. It brought together representatives from the relevant ministries and public institutions including MoFA, MESTI, NDPC, private sector entities and farmer-based organizations. The Action Plan defined implementation programmes in the respective agro- ecological zones and in the various districts. Activities defined in the action plan have been developed on the premise that the eight programme areas of the Agriculture and Food Security focus area of the NCCP, provide a useful framework for detailing the specific activities and their corresponding implementing agencies. Other key components discussed the cross-cutting issues in the implementation of the plan and the monitoring and evaluation system. What remains crucial now is the allocation of resources to effectively implement the plan. In this regards, the lessons from the prioritization of the action areas by the stakeholders are instructive. Each of the three agro-ecological zones has action areas of emphasis. However, the development and promotion of climate-resilient cropping systems is important for all three zones and national efforts to focus on this since it is at the foundation of food security. More specifically, for the Savannah Zone, water conservation and irrigation systems are critical. For the Transition Zone, the development of livestock production system is important whilst for the Forest Zone, capacity development is a priority. The key message from the prioritization is that, it guides the formulation of the location-specific activities to address climate change and therefore engenders effective allocation of national resources. What needs to be underscored is the fact that, it is not the formulation of plans that creates impact. It is the dedicated implementation and commitment to the ideals and principles undergirding the plans that bring results. The earnest hope is to have commitment manifested with this national action plan.